Parental Age and Risk of Infant Leukaemia: A Pooled Analysis. Issue 6 (22nd September 2017) - Marcotte, Erin L.; Druley, Todd E.; Johnson, Kimberly J.; Richardson, Michaela; von Behren, Julie; Mueller, Beth A.; Carozza, Susan; McLaughlin, Colleen; Chow, Eric J.; Reynolds, Peggy; Spector, Logan G.
Abstract: Background: Infant leukaemia (IL) is extremely rare with fewer than 150 cases occurring each year in the United States. Little is known about its causes. However, recent evidence supports a role of de novo mutations in IL aetiology. Parental age has been associated with several adverse outcomes in offspring, including childhood cancers. Given the role of older parental age in de novo mutations in offspring, we carried out an analysis of parental age and IL. Methods: We evaluated the relationship between parental age and IL in a case–control study using registry data from New York, Minnesota, California, Texas, and Washington. Records from 402 cases [219 acute lymphoblastic leukaemia (ALL), 131 acute myeloid leukaemia (AML), and 52 other] and 45 392 controls born during 1981–2004 were analysed. Odds ratios (OR) and 95% confidence intervals (CI) were calculated by logistic regression. Estimates were adjusted for infant sex, birth year category, maternal race, state, and mutually adjusted for paternal or maternal age, respectively. Results: Infants with mothers' age ≥40 years had an increased risk of developing AML (OR 4.80, 95% CI 1.80, 12.76). In contrast, paternal age <20 was associated with increased risk of ALL (OR 3.69, 95% CI 1.62, 8.41). Conclusion: This study demonstrates increased risk of infant ALL in relation to young paternal age. Given record linkage, there is little concern with recall or selection bias, although data are lacking on MLL gene status and other potentially important variables. Parent of origin effects, de novo mutations, and/or carcinogenic exposures may be involved in IL aetiology.